Music Studies in the New Millennium: Perspectives from Canada - Shepherd, John (Canadian University Music Review / Revue de musique des universités canadiennes, 2000)
Canada and the Canadian University Music Review have proved fertile grounds for the development of progressive music scholarship since the 1970s. Such developments had to counter the weight of history, which supported established and securely institutionalized forms of academic music. Yet these progressive developments in turn benefitted from major social and cultural shifts, such as those of the Depression years and of "the sixties." A crucial lever and sustaining force in major developments in progressive music scholarship that were to occur from the 1970s onward was critical theory. Theory now pervades much academic work in music, and has given rise to more sophisticated and varied approaches than was possible in the 1970s. The essays in this volume evidence this sophistication and variety, and bear witness to the way in which the intellectual and social topography of Canada can be argued to have proved especially nurturing to progressive scholarship in music.